Morphological changes of thymus in immature rats following inhalation exposure of toluene. - Voloshin, V. N. (Морфологія / Morphologia / Morfologìâ, 2012)
The aim of this study was to determine characteristics histological structure of the thymus of rats following inhalation exposure to toluene concentrations of 500 mg/m3 for 2 months. The experiment used white laboratory rats with initial body weight of 40-50 g, the studied area of the cortex and medulla of the thymus and their relationship. We calculated quantitatively in lymphoid cell populations of the body at different times after termination of the action of the studied factors. It is established that the effect of inhalation of toluene causes accidental thymus involution phenomena. In the action of toluene in different parts of the thymus observed phenomena toxicity and compensatory-adaptive changes. Longer after pre-reduction of toluene reduces the differences between histological performance of the experimental and control groups.